Regulation of the fructose transporter GLUT5 in health and disease - Douard, Veronique (American Physiological Society, 2008)
Fructose is now such an important component of human diets that increasing attention is being focused on the fructose transporter GLUT5. In this review, we describe the regulation of GLUT5 not only in the intestine and testis, where it was first discovered, but also in the kidney, skeletal muscle, fat tissue, and brain where increasing numbers of cell types have been found to have GLUT5. GLUT5 expression levels and fructose uptake rates are also significantly affected by diabetes, hypertension, obesity, and inflammation and seem to be induced during carcinogenesis, particularly in the mammary glands. We end by highlighting research areas that should yield information needed to better understand the role of GLUT5 during normal development, metabolic disturbances, and cancer.